The Effect of Tourism Facilities on the Level of Visitor Satisfaction at the Tourism Object of Bintang Galesong Beach Bathing, Takalar Regency - Awaliya, Iis Nur; Muhammad Darwis; Didin Halim (Business Research and Administration Innovation, 2025)
This study aims to determine the effect of tourist facilities on the level of visitor satisfaction in the object of research on Bintang Galesong Beach Baths, Takalar Regency. This study uses a type of quantitative research. Data collection techniques were carried out through observation, questionnaires and documentation. The sample used in this study was 83 respondents. The data obtained from the research results were processed using data analysis and using the help of the SPSS version 25 software program which consisted of validity tests and reliability tests on research instruments, descriptive data analysis techniques and inferential statistical analysis. The results of the study show that the indicators used for each of these variables indicate where tourism facilities are in the good category. For indicators on the variable level of visitor satisfaction is in the good category. based on the correlation test there is a strong/high relationship, so it can be concluded that there is a significant influence between tourist facilities on the level of visitor satisfaction at the Bintang Galesong beach bathing object, Takalar Regency.